Doping vulnerabilities, rationalisations and contestations: The lived experience of national level athletes. Issue 4 (June 2017) - Whitaker, L.; Backhouse, S.H.; Long, J.
Highlights: Doping is often driven by a need to 'keep up' rather than enhance performance. Athletes can rationalise doping based on the behaviour of others. Acting in the belief that everyone else is doping can help fulfil the prophecy. Being aware of alternatives can protect athletes from doping. Sport organisations need to be equipped to buffer against periods of instability. Abstract: Behaviour is shaped by the interactions between a person, their social sphere and their environment. Yet research into doping in sport has largely focused on the athlete and the individual factors that influence prohibited substance use. Owing to the stigma associated with doping, it can be difficult to undertake research with those who have committed anti-doping rule violations. However, a lot can be learnt from the experiences and reflections of those who are immersed within a specific context and sporting environment. Therefore, the purpose of this study was to explore national level athletes' perceptions of what influences willingness to dope in athletics and rugby league. Through semi-structured interviews, nine national level athletes drew upon their sporting histories to identify specific situations in their sport where they thought athletes might be willing to dope. Whilst considering the behaviour of others, they also drew upon their own personal experiences and the resources available to them as national level athletes to consider how these might give rise to doping vulnerability. In doing so, participants were empathetic and shared their perceptions of why some athletes might intentionally dope in their sport. These shared perceptions further our understanding of the complexity of doping in sport and underscore the importance of optimising the environment in order to help athletes cope with the demands of sport and thwarting the development of a self-fulfilling prophecy.